UJI KADAR FLUORIDA DALAM AIR MINUM KEMASAN TAHUN 2015 - Fadella Vilutama; Ferry Kriswandana; Darjati . (GEMA LINGKUNGAN KESEHATAN, 2016)
Studies in the Harvard School of Public Health (HSPH) and the China Medical University of Shenyang in 2012 showed that fluorides beyond the standard levels defined in the United States (0.7 to 1.2 mg/L) are capable of affecting IQ of children. Therefore, fluoride levels in drinking water in Indonesia need to be controlled. The purpose of the present study was to determine the levels of fluoride in drinking water in accordance with the SNI 01-3553-2006 regarding Bottled Drinking Water.  The present study was a descriptives research. Samples were taken at Supermarket C and examined at the Center for Health Laboratory Surabaya. Data were tabulated and descriptively analyzed.  Result showed that the samples examined did not qualify the SNI 01-3553-2006 regarding Bottled Drinking Water. The excessive levels of fluoride may cause public health problems. One of these health problems is dental fluorosis, a decrease in IQ of children and an increase in the risk of fractures. The levels of fluoride in bottled drinking water in the study ranged from the smallest 0.907 mg/L to the largest 1.498 mg/L. The future researchers are recommended to study the effectiveness of bio-carbon filters from the plant Tridax procumbens to eliminate the levels of fluoride in drinking water with temperature variations.